Electronic monitoring in Spain: analysis of the GPS implementation in cases of gender violence - Arenas-García, Lorea (My University, 2016)
The implementation of the Global Positioning Systems (GPS) in the surveillance and monitoring of offenders by public institutions has grown exponentially since 2005. His presence appears related to the social alarm in the public opinion caused by certain crimes (Peckenpaugh, 2006) and, at the same time, to the need of containing dangerous and serious offenders, as well as technological advances that innovate new forms of crime control, reformulating sentences and traditional measures. Spanish GPS technology began to be implemented in 2009 to control offenders who serve a restraining order in cases of gender violence. After seven years from this pilot experience there is no research that estimates their impacts and challenges of the measure. This paper examines the systems implementation during the first four years in order to determine their impacts and effectiveness. To this end it has applied a qualitative methodology based on in-depth interviews to a representative sample of institutional key actors who manage the restraining order throughout the Spanish territory, that is: police officers, judges, prosecutors, members of private companies, etc. The main results show a positive assessment of the measure while many technical problems have been referred.
Keywords: Violencia familiar; Electronic monitoring; Gender violence; GPS